2010
DOI: 10.3130/jaabe.9.171
|View full text |Cite
|
Sign up to set email alerts
|

Observations on Primary School Children′s Behavior after School by Using the Global Positioning System

Abstract: Empirical studies of human behavior have been developed mainly using methods of interview or questionnaire by researchers themselves. These studies have successfully obtained adequate results. To observe the behavior of many subjects at once, for many hours and in a wide area however, an alternative technological method is required. The purpose of the authors' work is to develop a better objective method based on measurements, observations and experiments to clarify human behavior in urban environments. The pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Moreover, regarding the exterior areas of buildings to minimize spots related to fear of crime, the outer walls of school buildings should be straight Troy and Grove, 2008) suggested that vegetation is related to crime, this study did not consider vegetation in the analysis because applying this element to a visibility graph analysis cannot be done accurately, and there were no clear criteria for determining whether certain vegetation interferes with visibility. In addition, as the children in the survey were too young to pinpoint the exact locations in which they feared crime, using a technological method such as a global positioning system (GPS) could improve the validity of the study (Sugihara et al, 2010). This study provides the evidence of effects of visibility on fear of crime in environments, and builds on previous research about fear of crime and environments in a more precise manner through its use of automated quantitative analysis techniques.…”
Section: Discussionmentioning
confidence: 83%
“…Moreover, regarding the exterior areas of buildings to minimize spots related to fear of crime, the outer walls of school buildings should be straight Troy and Grove, 2008) suggested that vegetation is related to crime, this study did not consider vegetation in the analysis because applying this element to a visibility graph analysis cannot be done accurately, and there were no clear criteria for determining whether certain vegetation interferes with visibility. In addition, as the children in the survey were too young to pinpoint the exact locations in which they feared crime, using a technological method such as a global positioning system (GPS) could improve the validity of the study (Sugihara et al, 2010). This study provides the evidence of effects of visibility on fear of crime in environments, and builds on previous research about fear of crime and environments in a more precise manner through its use of automated quantitative analysis techniques.…”
Section: Discussionmentioning
confidence: 83%
“…Based on the distance from elementary school criterion, 516 cases (88.97%) of "fear of crime" and 68 cases (81.93%) of "actual crime" occurred within 500 m of schools. A previous study indicated the trajectory of walking elementary students within the school district (Sugihara et al, 2010). In the present study, results by target district were as follows.…”
Section: Geographical Analysis 41 Fear Of Crime and Actual Crimementioning
confidence: 53%
“…Thus, elementary students are at increasing risk because most are confined to a specific school range primarily connecting the school they attend and their homes. In addition, most walk on streets (Sugihara et al, 2010). Previous studies indicate the negative effects of constant exposure to social crimes on adolescents' development and adaptability (Attar & Guerra, 1994;Fitzpatrick & Boldizar, 1993;Jenkins & Bell, 1994;Martinez & Richters, 1993).…”
Section: Introduction 11 Backgroundmentioning
confidence: 99%
“…Nomura and Kishimoto (2006) 2) demonstrated the efficiency of using GPS and GIS in analyzing visitors' behavior and activity through their experiment at a famous sightseeing area in Kamakura City. With their observations of primary school children's behavior after school, Sugihara, Matsushita, and Mumemoto (2010) 3) have developed a more effective method for clarifying human behavior in urban environments, using GPS, compared with the previous interview and questionnaire methods.…”
Section: Introductionmentioning
confidence: 99%